Developing Reading Skills Through Green Curriculum Implementation as an Instructional Model - Sondang Pondan Leoanak (Acitya: Journal of Teaching and Education, 2022)
This paper aims to investigate the implication of implementing green curriculum as an instructional model to increase English reading skills of the third semester students of Animal Feed Technology study program of Livestock department in the State Polytechnic of Agriculture Kupang (Politani) – NTT province. Additionally, students’ perception on the application of green curriculum in increasing their reading skills also measured. For this purpose, the mixed method research design was applied as a mean to explore the information about students’ knowledge and skills on English reading text before and after the application of green curriculum learning innovation. There were two groups of students: the experimental group (was facilitated using green curriculum teaching approach) and the control group (received conventional teaching strategy). The study reveals that, the students who received the application of green curriculum as learning innovation achieved better reading skills than those who did not receive any application of such teaching innovation. They also agreed that green curriculum application increased, supported and encouraged their competence in reading English text.